Gender Smart Agriculture for Equality and Empowerment - Huyer, Sophia; Gondwe, Therese; Diabate, Fatoumata; Kwaw, Adams; Mujawamariya, Gaudiose; Mapedza, Everisto D.; Mudege, Netsay; Adamaa, Faustina; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A detailed guide to the gender smart agriculture framework, including design, implementation, and assessment. A Gender-Smart Agriculture (GSA) approach takes into account women’s priorities and access to technology, resources, and information to facilitate climate resilience through equality and agency.